Diversion of The Brantas River Flow to The Porong River - Kusmaharti, Ratih; Sapto, Ari; Agung, Dewa Agung Gede (Yupa: Historical Studies Journal, 2024)
As an archipelago country, maritime culture has been rooted in the history of Indonesian tradition. River utilization and control of the ocean have become the veins of the economy. Changes in the shape of the river will also affect what happens around it. The Brantas River, as one of the centers of culture and civilization in East Java, has extraordinary dynamics which has rapid flow and contain many streams. Further, the existence of the Brantas River has also become the economic lifeblood of the people of East Java. This research discusses changes to the Brantas river flow in the Porong branch. Changes in the Porong river branch occur doe to natural factors and human modification. The result of the research show that modifications to the river flow carried out by the government at the time changed the direction of the river flow, the function of the river and the economic pattern of society in East Java.